Potential of the Hotel and Resort Accommodation Industry in East Lombok District, West Nusa Tenggara Province - Sendi Rahman Maulana; Nabila Marsha Nada; Titus Indrajaya (Language Assistance, 2024)
Tourism is an industrial sector that increases foreign exchange and the country's economy. Indonesia has natural potential which is the main reference in the tourism sector in Indonesia. Apart from natural potential, Indonesia also has beautiful islands, and has various ethnic and cultural characteristics, so it is able to attract tourists, both local and foreign. One of the islands that is the main destination for domestic and foreign tourists is Lombok Island. Lombok Island is rich in natural tourism that is still natural and cultural values that still maintain their authenticity. Lombok Island is an island in West Nusa Tenggara Province, Indonesia. Overall, Lombok has great potential to become a leading destination in the accommodation sector in Indonesia, with a focus on developing quality and sustainable hotels and resorts. This writing method uses literature review and uses qualitative research. This writing aims to (1) determine the potential of the hotel and resort accommodation industry in East Lombok, (2) determine the readiness of the city of East Lombok for the hotel and resort accommodation industry.